Geospatial data of freshwater habitats for macroecological studies: an example with freshwater fishes. Issue 1 (2nd January 2016) - González Vilas, Luis; Guisande, Cástor; Vari, Richard P.; Pelayo-Villamil, Patricia; Manjarrés-Hernández, Ana; García-Roselló, Emilio; González-Dacosta, Jacinto; Heine, Jürgen; Pérez-Costas, Elisa; Granado-Lorencio, Carlos; Palau-Ibars, Antoni; Lobo, Jorge M.
Abstract : Global data sets are essential in macroecological studies. File formats of the few available data sets of freshwater ecosystems, however, are either incompatible with most macroecological software packages, incomplete, or of coarse spatial resolutions. We integrated more than 460 million geographical coordinates for freshwater habitats in the FRWater data set, partitioned into seven different habitats (lentic, wetlands, reservoirs, small rivers, large rivers, small ditches, large ditches, small channels, large channels, small drains and large drains) in ModestR (http://www.ipez.es/ModestR ). A comprehensive collection of geospatial rasters was assembled, one for each of the seven freshwater habitats, with the area in km 2 occupied by each habitat presented in cells of 5 arc-minute resolution. The utility of FRWater was evaluated using hierarchical partitioning via the identification of the contribution of the seven different freshwater habitats to both species richness and rarity. To this end, we used a data set of 836, 123 geographical records of the 16, 216 species of freshwater fishes recognized as valid by systematists at the end of 2014. Areas in North America and Europe are the most detailed in the FRWater data set, evidencing the higher quality of data sources in those regions. The number of geographical coordinates is much lower for Africa, Asia, Australia, and South America where many water bodies remain unmapped. In light of the variation in information quality at continental levels, we performed and present comparative analyses for Europe versus South America at local (5ʹ × 5ʹ grid cells) and regional (5° × 5° grid cells) scales. The relative contribution of small rivers to both species richness and rarity was highest under almost all analyses, followed by lentic habitats and large rivers. The areas of different habitats moreover explained a relatively high proportion of the observed variance in geographic rarity. Our findings corroborate previous findings that the greater contribution of small rivers to species richness is probably due to these habitats promoting geographical rarity. Hence, species richness is favored by the isolation resultant from, and the refuges associated with, small river basins and via the diversification processes promoted by such isolation.